2012
DOI: 10.3109/1354750x.2012.658864
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of serum chemerin in patients with obstructive sleep apnea syndrome

Abstract: Elevated serum chemerin levels could be an independent predicting marker of the presence and severity of OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Clinical studies have shown that patients with MetS have higher levels of chemerin than those without MetS and present an association with BMI, serum triglycerides, and blood pressure. 31 A recent case-control study with a moderately obese Asian population showed that OSA patients had higher chemerin levels and found a weak but positive correlation with sleep apnea severity and WC and BMI 32 ; in this study chemerin was also correlated with inflammation and hypothesized as a possible a link between adipose tissue, OSA, and inflammation. These results could not be confirmed in our morbidly obese population with high indices of insulin resistance, where we found that central obesity had a stronger effect than OSA.…”
Section: Discussionmentioning
confidence: 75%
“…Clinical studies have shown that patients with MetS have higher levels of chemerin than those without MetS and present an association with BMI, serum triglycerides, and blood pressure. 31 A recent case-control study with a moderately obese Asian population showed that OSA patients had higher chemerin levels and found a weak but positive correlation with sleep apnea severity and WC and BMI 32 ; in this study chemerin was also correlated with inflammation and hypothesized as a possible a link between adipose tissue, OSA, and inflammation. These results could not be confirmed in our morbidly obese population with high indices of insulin resistance, where we found that central obesity had a stronger effect than OSA.…”
Section: Discussionmentioning
confidence: 75%
“…However, Feng et al . examined chemerin levels in patients with obstructive sleep apnea syndrome (OSAS) and found that serum chemerin levels were positively correlated with CRP and the severity of OSAS, supporting the relationship between chemerin levels and inflammation . Gisondi et al .…”
Section: Discussionmentioning
confidence: 89%
“…There are no other studies of chemerin and COPD in the literature. However, Feng et al examined chemerin levels in patients with obstructive sleep apnea syndrome (OSAS) and found that serum chemerin levels were positively correlated with CRP and the severity of OSAS, supporting the relationship between chemerin levels and inflammation (24). Gisondi et al revealed a linear correlation between chemerin and CRP levels in patients with chronic plaque psoriasis (25).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OSA and these factors however remain unclear. Previous studies on adiponectin and apelin levels in OSA patients report conflicting results (21)(22)(23)(24) while other few focusing on chemerin and SFRP5 in OSA patients, have been limited by the absence of multivariate adjustment or a smaller sample size (25,26). Furthermore, the relationship between these adipokines and IMT among OSA patients was not clarified.…”
Section: Introductionmentioning
confidence: 98%